Negative electrode material and preparation method thereof, negative electrode plate, battery and electric equipment

By distributing carbon nanofibers and silicon-based materials in the pores of the carbon matrix to form a mesh structure, the performance problems caused by volume expansion of the silicon negative electrode material are solved, and the high conductivity and capacity performance are improved, and the cycle life of the battery is extended.

CN119920822APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The volume of the silicon negative electrode material expands during lithium embedding, resulting in pulverization, SEI film growth and electrical contact deterioration, limiting its application in lithium-ion batteries.

Method used

By distributing carbon nanofibers in the pores of the carbon matrix and distributing silicon-based materials on the carbon nanofibers, a mesh structure is formed, the conductivity is improved, and volume expansion is buffered through the porous structure of the carbon matrix.

Benefits of technology

It improves the conductivity and capacity performance of the negative electrode material, extends the cycle life of the battery, and enhances the fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920822A_ABST
    Figure CN119920822A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a preparation method thereof, a negative electrode plate, a battery and electric equipment. The negative electrode material comprises an inner core and a carbon coating layer coating the outer part of the inner core, wherein the inner core comprises a carbon matrix with a porous structure; the carbon nanofibers are located in pores of the carbon matrix, and the carbon nanofibers are mutually crosslinked to form a net-shaped structure; and the silicon-based material is distributed in pores of the carbon matrix and on the carbon nanofibers. According to the negative electrode material disclosed by the invention, through the reticular carbon nanofibers distributed in the pores of the carbon matrix and the silicon-based material distributed in the carbon nanofibers and the pores of the carbon matrix, the capacity performance of the negative electrode material is improved, and meanwhile, the carbon nanofibers form a large number of conductive paths, so that the conductivity of the negative electrode material is effectively improved; and the porous structure of the carbon matrix provides a buffer space for the volume expansion of the silicon-based material in the charge-discharge process, and the negative electrode material is prevented from falling off, so that the capacity performance and the cycle stability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of new energy technology, and specifically relates to a negative electrode material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device. Background Art

[0002] Silicon negative electrode material has a high theoretical capacity of about 3578mAh / g, but the volume expansion of silicon negative electrode material will be about 320% during the lithium insertion process, while graphite is only 12%. Large volume expansion will induce silicon particle pulverization, continuous growth of SEI film and poor electrical contact, causing the capacity of silicon negative electrode to decay rapidly. In addition, the electrical conductivity of silicon is poor, only 10 -4 ~10 -3 S / cm, which further limits the application of silicon materials in lithium-ion batteries.

[0003] Since carbonaceous materials have good flexibility and small volume changes during the process of lithium ion insertion and extraction, they can be used as active substances to combine with lithium and provide channels for lithium ions to enter and exit. In related technologies, silicon-carbon composites are used to improve the high volume expansion and poor conductivity of silicon negative electrodes. The current mainstream preparation method is to use CVD to deposit nanosilicon in porous carbon. However, most of the generated nanosilicon is deposited on the inner wall of the porous carbon and continues to accumulate, so that the obtained silicon-carbon negative electrode material still has the problem of poor conductivity, resulting in poor battery performance of silicon-carbon negative electrode materials. Summary of the invention

[0004] In view of the above-mentioned defects or deficiencies in the prior art, it is desired to provide a negative electrode material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device. The negative electrode material improves the capacity performance of the negative electrode material through the mesh carbon nanofibers distributed inside the pores of the carbon matrix, and the silicon-based material distributed on the carbon nanofibers. At the same time, the carbon nanofibers form a large number of conductive paths, which effectively improve the conductivity of the negative electrode material. The porous structure of the carbon matrix provides a buffer space for the volume expansion of the silicon-based material during the charging and discharging process, thereby preventing the negative electrode material from falling off.

[0005] In a first aspect, the present invention provides a negative electrode material, comprising a core and a carbon coating layer coated on the outside of the core; wherein the core comprises: A carbon matrix having a porous structure; The carbon nanofibers are located inside the pores of the carbon matrix, and the carbon nanofibers are cross-linked to form a network structure in the porous carbon pores; Silicon-based materials are distributed inside the pores of the carbon matrix and on the carbon nanofibers.

[0006] As an option, the pores of the carbon matrix have a pore diameter of 30 nm to 500 nm.

[0007] As an option, the average particle size of the carbon matrix is ​​2 μm-30 μm.

[0008] As an optional solution, the length of the carbon nanofiber is 20nm-1000nm, and the diameter of the carbon nanofiber is 10nm-100nm.

[0009] As an optional solution, based on the mass of the negative electrode material, the mass percentage of the silicon-based material is 30%-95%.

[0010] As an optional solution, the average particle size of the silicon-based material is 2nm-10nm.

[0011] As an alternative, the specific surface area of ​​the negative electrode material is 2m 2 / g-5m 2 / g.

[0012] As an optional solution, the median particle size of the negative electrode material is 5 μm-40 μm.

[0013] As an optional solution, the carbon nanofibers are also distributed on the surface of the carbon matrix, and both ends of the carbon nanofibers located on the surface of the carbon matrix are in contact with the carbon matrix and the carbon coating layer respectively.

[0014] As an optional solution, the thickness of the carbon coating layer is 10 nm-2000 nm.

[0015] In a second aspect, the present invention provides a method for preparing the negative electrode material of the first aspect, comprising: The carbon matrix and the catalyst are introduced into a reducing gas and a carbonaceous gas under the protection of an inert gas, and subjected to a heat treatment to obtain a first product; wherein the carbonaceous gas includes a gas that can be cracked to obtain carbon after the heat treatment; The first product is introduced into a gaseous silicon source and subjected to heat treatment to obtain a second product; The second product is carbon-coated to obtain a negative electrode material.

[0016] As an optional solution, the carbon matrix and the catalyst are introduced into a reducing gas and a carbonaceous gas under the protection of an inert gas, and heat-treated to obtain a first product, including: The carbon matrix and the catalyst are heated to a first temperature at a first heating rate and maintained under the protection of an inert gas. After a reducing gas is introduced for a first period of time, a carbonaceous gas is introduced while the reducing gas is maintained, and heat treatment is performed for a second period of time to obtain a first product.

[0017] As an optional solution, the first heating rate is 2°C / min-10°C / min, the first temperature is 500°C-800°C, the first time length is 10min-20min, and the second time length is 0.5h-1.5h.

[0018] As an optional solution, the flow rate of the reducing gas is 0.5L / min-2L / min, and the flow rate of the carbonaceous gas is 0.5L / min-2L / min.

[0019] As an optional solution, the flow ratio of the inert gas to the carbonaceous gas is (0.1:9.9)-(9.9:0.1).

[0020] Alternatively, the carbonaceous gas includes methane and / or acetylene.

[0021] As an optional scheme, the catalyst includes at least one of a metal iron salt, a metal cobalt salt, a metal nickel salt and a metal copper salt.

[0022] As an optional scheme, the catalyst includes at least one of ferric chloride, cobalt chloride, cupric chloride, cobalt nitrate, nickel nitrate, nickel acetate, and copper sulfate.

[0023] As an optional solution, based on the mass of the carbon matrix, the mass percentage of the catalyst is 0.1%-5%.

[0024] As an optional solution, before introducing the gaseous silicon source into the first product and heat treating it to obtain the second product, the method further includes: The first product is sequentially acid-washed, water-washed, and dried.

[0025] As an optional solution, the first product is introduced into a gaseous silicon source and heat-treated to obtain a second product, comprising: The first product is heated to a second temperature at a second heating rate and maintained under the protection of an inert gas, and then a gaseous silicon source is introduced to carry out a constant temperature reaction for a third time period.

[0026] As an optional solution, the second heating rate is 0.2°C / min-10°C / min, the second temperature is 500°C-800°C, and the third time is 0.1h-10h.

[0027] As an optional option, the third duration is 1h-4h.

[0028] As an optional solution, the flow rate of the gaseous silicon source is 1L / min-5L / min; As an option, the gaseous silicon source includes at least one of monosilane, disilane, monochlorosilane and dichlorosilane.

[0029] As an optional solution, the second product is carbon-coated to obtain a negative electrode material, including: The second product and the carbon precursor are mixed and calcined to obtain the negative electrode material; wherein the mass ratio of the carbon precursor to the second product is 1:(0.5-3).

[0030] In a third aspect, the present invention provides a negative electrode sheet comprising a current collector and the negative electrode material of the first aspect.

[0031] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet of the third aspect.

[0032] In a fifth aspect, the present invention provides an electrical device, comprising the battery of the fourth aspect, wherein the battery supplies power to the electrical device.

[0033] The negative electrode material provided by the present invention has carbon nanofibers distributed inside the pores of the carbon matrix, and the carbon nanofibers are cross-linked to form a network structure. On the one hand, the carbon nanofibers can provide attachment sites for the silicon-based material, and on the other hand, the carbon nanofibers with a network structure form a large number of conductive paths inside the carbon matrix, which effectively improves the conductivity of the negative electrode material, thereby helping to improve the fast charging performance of the battery; and the porous structure of the carbon matrix provides a buffer space for the volume expansion of the silicon-based material during the charging and discharging process, thereby avoiding separation of the negative electrode material from the current collector; the carbon coating layer is beneficial to isolating the silicon-based material from the electrolyte, avoiding direct contact between the silicon-based material and the electrolyte, thereby helping to improve the cycle performance of the battery; in short, the negative electrode material of the present invention has high capacity performance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 A schematic diagram of the structure of a negative electrode material according to an embodiment of the present application; Figure 2 This is an electron microscope photograph of the negative electrode material of Example 1; Figure 3 This is the first charge and discharge curve of the battery in Example 1.

[0035] In the figure, 1. Silicon-based materials, 2. Carbon nanofibers, 3. Pores, 4. Carbon matrix, 5. Carbon coating. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below.

[0038] In a first aspect, an embodiment of the present application provides a negative electrode material, comprising a core and a carbon coating layer 5 coated outside the core; wherein the core comprises: A carbon matrix 4 having a porous structure; The carbon nanofibers 2 are located inside the pores 3 of the carbon matrix 4, and the carbon nanofibers 2 are cross-linked to form a network structure inside the pores of the carbon matrix 4; The silicon-based material 1 is distributed inside the pores 3 of the carbon matrix 4 and on the carbon nanofibers 2 .

[0039] Among them, the carbon matrix 4 can be any kind of porous carbon material; in a specific embodiment, the carbon matrix 4 can be a porous carbon directly purchased commercially. Of course, the carbon matrix 4 can also be a carbon material with a porous structure prepared by a template method or heat treatment method; in some other embodiments, the carbon matrix can also be oxidized so that its surface contains hydroxyl, carboxyl or other oxygen-containing functional groups, which is beneficial to improve the wettability of the carbon matrix; in a preferred embodiment, the carbon matrix has abundant nanopores, and the carbon matrix is ​​not oxidized, which is beneficial to avoid excessive attachment of the catalyst, resulting in excessive growth of carbon nanofibers and clogging the pores of the carbon matrix.

[0040] The silicon-based material may be, but is not limited to, a nano-silicon material, a silicon-carbon composite material, or a silicon-oxygen composite material.

[0041] The carbon nanofibers include carbon nanowires and / or carbon nanotubes, wherein the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; the carbon nanofibers include at least one of whisker-shaped, branched, bidirectional, multidirectional, spiral, and helical shapes.

[0042] The carbon coating can be used to improve the conductivity of the negative electrode material on the one hand, and on the other hand, it can also block the contact between the electrolyte and silicon, thus preventing the electrolyte from corroding the silicon.

[0043] The negative electrode material of the embodiment of the present application solves the problem of poor conductivity of silicon-carbon composite materials in the prior art. The embodiment of the present application, by distributing carbon nanofibers inside the pores of the carbon matrix, and the carbon nanofibers are cross-linked to form a mesh structure, the carbon nanofibers can provide attachment sites for the silicon-based material on the one hand, and on the other hand, the carbon nanofibers with a mesh structure form a large number of conductive paths inside the carbon matrix, which effectively improves the conductivity of the negative electrode material, thereby helping to improve the fast charging performance of the battery; and the porous structure of the carbon matrix provides a buffer space for the volume expansion of the silicon-based material during the charging and discharging process, avoiding the separation of the negative electrode material from the current collector; the carbon coating layer is conducive to isolating the silicon-based material from the electrolyte, avoiding direct contact between the silicon-based material and the electrolyte, thereby helping to improve the cycle performance of the battery; in short, the negative electrode material of the present invention has high capacity performance and conductivity.

[0044] As an achievable manner, the pores of the carbon matrix have a pore diameter of 30 nm to 500 nm.

[0045] Specifically, the pore size of the carbon matrix can be, but is not limited to, 30 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm, etc. When the pore size of the carbon matrix is ​​less than 30 nm, the generated carbon nanofibers will cause the blockage of the nanopores, which is not conducive to the deposition of silicon; when the pore size of the carbon matrix is ​​greater than 500 nm, the porous carbon matrix will become loose, which is easy to cause structural collapse.

[0046] In this embodiment, the pores of the carbon matrix are nanopores, which are beneficial to the growth of carbon nanofibers and also beneficial to improving the ion transport performance of the negative electrode material.

[0047] As an achievable manner, the average particle size of the carbon matrix is ​​2 μm to 30 μm.

[0048] Specifically, the average particle size of the carbon matrix is ​​2 μm, 5 μm, 10 μm, 12 μm, 15 μm, 20 μm, 22 μm, 25 μm or 30 μm, etc. When the average particle size of the carbon matrix is ​​less than 2 μm, it is not conducive to the growth of carbon nanofibers and the deposition of nanosilicon; when the average particle size of the carbon matrix is ​​greater than 30 μm, the particle size of the prepared negative electrode material will be larger, the migration path of lithium ions will become longer, and the rate performance of the battery will be weakened.

[0049] The average particle size of the carbon matrix in this embodiment is conducive to uniform dispersion of the negative electrode material, reliable attachment of the negative electrode material to the current collector, and sufficient contact with the electrolyte, thereby avoiding problems such as extended lithium ion transmission channels and falling off of the negative electrode material.

[0050] As an achievable manner, the length of the carbon nanofiber is 20 nm-1000 nm, and the diameter of the carbon nanofiber is 10 nm-100 nm.

[0051] Specifically, the length of the carbon nanofibers can be but is not limited to 20nm, 40nm, 60nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, etc.; when the length of the carbon nanofibers is less than 20nm, it is not conducive to building an interconnected electronic network between nanosilicon; when the length of the carbon nanofibers is greater than 1000nm, the generated carbon nanofibers will seriously block the porous structure, which is not conducive to the deposition of nanosilicon.

[0052] The diameter of the carbon nanofiber can be but is not limited to 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or 200nm; when the diameter of the carbon nanofiber is less than 10nm, the process is difficult to implement and the manufacturing cost is increased; when the diameter of the carbon nanofiber is greater than 200nm, the generated carbon nanofiber will block the porous structure, which is not conducive to the deposition of nanosilicon and the construction of an electronic conduction network between nanosilicon.

[0053] The length and particle size of the carbon nanofibers in this embodiment are controllable, and the integration of the carbon nanofibers and the porous carbon matrix is ​​achieved by in-situ constructing a cross-linked carbon nanofiber network in the pore structure of the porous carbon, which is beneficial to the rapid transport of electrons.

[0054] As an achievable approach, based on the mass of the negative electrode material, the mass percentage of the silicon-based material is 30%-95%.

[0055] The mass percentage of the silicon-based material in this embodiment is conducive to ensuring that the negative electrode material has higher capacity performance and conductivity.

[0056] Specifically, the mass percentage of the silicon-based material can be but is not limited to 30%, 40%, 50%, 60%, 70%, 80%, 90% or 95%. When the mass percentage of the silicon-based material is lower than 30%, the content is low, resulting in poor capacity performance of the negative electrode material; when the mass percentage of the silicon-based material is higher than 95%, the content is high, resulting in poor conductivity of the negative electrode material. At the same time, the volume of the silicon-based material expands during the charge and discharge process, which easily causes the negative electrode material to fall off.

[0057] In some embodiments, the average particle size of the silicon-based material is 2 nm to 10 nm.

[0058] The average particle size of the silicon-based material in this embodiment is conducive to uniform dispersion of the silicon-based material on the carbon nanofibers, thereby reliably improving the capacity performance of the negative electrode material.

[0059] Specifically, the average particle size of the silicon-based material can be but is not limited to 2nm, 5nm, 7nm, 8nm or 10nm. When the average particle size of the silicon-based material is less than 2nm, the average particle size is too small, which causes the silicon-based material particles to easily accumulate; when the average particle size of the silicon-based material is greater than 10nm, the average particle size is too large, and the pores of the carbon matrix cannot provide sufficient buffer space. During the charge and discharge process, the volume expansion of the silicon-based material may cause the negative electrode material to fall off.

[0060] In some embodiments, the specific surface area of ​​the negative electrode material is 2 m 2 / g-5m 2 / g.

[0061] The specific surface area of ​​the negative electrode material in this embodiment is conducive to the negative electrode material fully contacting with the electrolyte, while improving the transmission performance of lithium ions, and further conducive to improving the charge and discharge performance and cycle performance of the battery.

[0062] Specifically, the specific surface area of ​​the negative electrode material can be, but is not limited to, 2 m 2 / g, 3m 2 / g, 4m 2 / g or 5m 2 / g, when the specific surface area of ​​the negative electrode material is less than 2m 2 / g, the specific surface area is too small, which makes it difficult for lithium ions to be inserted and removed, reducing the cycle performance of the negative electrode material; when the specific surface area is greater than 5m 2 / g, the specific surface area is too large, which affects the lithium ion transmission performance.

[0063] In some embodiments, the negative electrode material has a median particle size of 5 μm to 40 μm.

[0064] The median particle size of this embodiment is conducive to the appropriate particle size of the negative electrode material and to shortening the transmission channel of lithium ions, thereby improving the cycle performance and charge and discharge performance of the battery.

[0065] Specifically, the median particle size of the negative electrode material is 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm, etc.; when the median particle size of the negative electrode material is less than 5μm, the particle size is too small, the contact area with the electrolyte is large, and a solid electrolyte film is easily formed, causing lithium ion loss and reducing the initial charge and discharge efficiency of the battery; when the median particle size of the negative electrode material is greater than 40μm, the particle size is too large, which easily causes the negative electrode material to pulverize and fall off, and cannot fully contact with the electrolyte, thereby reducing the battery's cycle performance and charge and discharge performance.

[0066] In some embodiments, the carbon nanofibers are also distributed on the surface of the carbon matrix, and both ends of the carbon nanofibers located on the surface of the carbon matrix are in contact with the carbon matrix and the carbon coating layer, respectively.

[0067] In some embodiments, the carbon coating layer has a thickness of 10 nm to 2000 nm.

[0068] The thickness of this embodiment is conducive to the carbon coating layer to reliably coat the inner core, avoiding direct contact between the silicon-based material and the electrolyte, and is also conducive to increasing the conductivity of the negative electrode material.

[0069] Specifically, the thickness of the carbon coating layer can be but is not limited to 10nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 1000nm, 1500nm or 2000nm, etc.; when the thickness of the carbon coating layer is less than 10nm, the carbon coating layer is too thin and cannot reliably isolate the silicon-based material and the electrolyte; when the thickness of the carbon coating layer is greater than 2000nm, the carbon coating layer is too thick, resulting in an increase in the transmission path of lithium ions.

[0070] As a feasible approach, the tap density of the negative electrode material is 0.5 g / cm 3 -1.2g / cm 3 .

[0071] Specifically, the tap density of the negative electrode material may be, but is not limited to, 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 or 1.2g / cm 3 wait.

[0072] As a practical approach, the true density of the negative electrode material is 1.3 g / cm 3 -2g / cm 3 .

[0073] Specifically, the true density of the negative electrode material may be, but is not limited to, 1.3 g / cm 3 , 1.5g / cm 3 , 1.7g / cm 3 , 1.9g / cm 3 or 2g / cm 3 .

[0074] In summary, the negative electrode material of the embodiment of the present application has carbon nanofibers distributed inside the pores of the carbon matrix, and the carbon nanofibers are cross-linked to form a network structure. On the one hand, the carbon nanofibers can provide attachment sites for the silicon-based material, and on the other hand, the carbon nanofibers with a network structure form a large number of conductive paths inside the carbon matrix, which effectively improves the conductivity of the negative electrode material, thereby helping to improve the fast charging performance of the battery; and the porous structure of the carbon matrix provides a buffer space for the volume expansion of the silicon-based material during the charging and discharging process, thereby avoiding separation of the negative electrode material from the current collector; the carbon coating layer is conducive to isolating the silicon-based material from the electrolyte, avoiding direct contact between the silicon-based material and the electrolyte, thereby helping to improve the cycle performance of the battery; in short, the negative electrode material of the present invention has high capacity performance and conductivity; Furthermore, the mass percentage, average particle size, and length and diameter of the carbon nanofibers of the silicon-based materials in the embodiments of the present application are further beneficial to improving the battery performance of the negative electrode material.

[0075] In a second aspect, the present invention provides a method for preparing the negative electrode material of the first aspect, comprising: S10, introducing a reducing gas and a carbonaceous gas into the carbon matrix and the catalyst under the protection of an inert gas, and heat-treating the carbon matrix and the catalyst to obtain a first product; wherein the carbonaceous gas includes a gas that can be cracked to obtain carbon after heat treatment; Among them, the inert gas includes at least one of nitrogen, argon, helium and neon; the reducing gas includes hydrogen; the catalyst can be a metal salt catalyst; the carbonaceous gas can be but is not limited to at least one of methane, ethane, propane, propylene, acetylene, natural gas, and gaseous styrene.

[0076] It should be noted that this step can be carried out in a chemical vapor deposition furnace. The inert gas is mainly used to remove oxygen from the reaction system. The catalyst is evenly dispersed on the carbon matrix. The reducing gas is used to promote the decomposition of the carbonaceous gas and prevent the catalyst from reacting with the carbonaceous gas to form metal carbides, which leads to catalyst poisoning, thereby helping to ensure the catalytic performance of the catalyst; the carbonaceous gas is used to grow carbon nanofibers with different directions and cross-linked to form a network structure inside the pores of the carbon matrix under the action of the catalyst.

[0077] In some embodiments, the carbon matrix can be first dispersed in a dispersant to obtain a suspension, the catalyst can be dispersed in the suspension, and after suction filtration and drying, the catalyst is dispersed on the carbon matrix and then heat treated; wherein the dispersant includes at least one of methanol, ethanol, propanol, n-propanol, isopropanol, isobutanol, and propylene glycol.

[0078] In a preferred embodiment, in this step, the oxygen content in the entire reaction system should be less than or equal to 200 ppm.

[0079] S20, introducing a gaseous silicon source into the first product and subjecting it to thermal treatment to obtain a second product; In this step, the gaseous silicon source is used as a precursor of the silicon-based material. After heat treatment, the silicon-based material can be deposited inside the pores of the carbon matrix and on the carbon nanofibers.

[0080] S30, carbon-coating the second product to obtain a negative electrode material.

[0081] It is understood that the carbon coating can be solid phase coating or liquid phase coating; wherein, solid phase coating refers to stirring or shaking the second product and the carbon precursor, and then calcining at high temperature; the stirring method can be but is not limited to ball milling and VC mixer mixing; Liquid phase coating refers to dispersing the second product and the carbon precursor in a dispersant, spray drying, and then calcining at a high temperature.

[0082] The carbon precursor may be, but is not limited to, at least one of needle coke, petroleum coke, asphalt, phenolic resin, urea-formaldehyde resin, polyamide resin, epoxy resin, polyethylene, polyvinyl alcohol, polyvinylidene fluoride, polyvinyl chloride, sucrose, and glucose.

[0083] The preparation method of the embodiment of the present application is simple to operate, can grow carbon nanofibers inside the pores of the carbon matrix, and can deposit silicon-based materials inside the pores of the carbon matrix and on the carbon nanofibers, thereby reliably obtaining a silicon-carbon composite negative electrode material.

[0084] In some embodiments, S20, introducing a reducing gas and a carbonaceous gas into the carbon matrix and the catalyst under the protection of an inert gas, and heat treating to obtain a first product, comprising: The carbon matrix and the catalyst are heated to a first temperature at a first heating rate and maintained under the protection of an inert gas. After a reducing gas is introduced for a first period of time, a carbonaceous gas is introduced while the reducing gas is maintained, and heat treatment is performed for a second period of time to obtain a first product.

[0085] In this embodiment, at a first temperature, introducing a reducing gas for a first period of time is beneficial to sufficient reduction of the catalyst. Introducing a reducing gas while introducing a carbonaceous gas is beneficial to ensuring that the carbonaceous gas reliably decomposes to grow carbon nanofibers, and avoiding oxidation of the carbonaceous gas at high temperature, which prevents the growth of carbon nanofibers.

[0086] In an optional embodiment, the carbon matrix and the catalyst are heated to a first temperature at a first heating rate and maintained under the protection of an inert gas. After the reducing gas is introduced for a first period of time, the carbonaceous gas is introduced while maintaining the introduction of the reducing gas for a predetermined period of time, and then the introduction of the carbonaceous gas is stopped and the heat treatment is continued for a second period of time to obtain a first product.

[0087] In some embodiments, the first heating rate is 2°C / min-10°C / min, the first temperature is 500°C-800°C, the first time length is 10min-20min, and the second time length is 0.5h-1.5h.

[0088] Specifically, the first heating rate can be but is not limited to 2°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min; the first temperature can be but is not limited to 500°C, 600°C, 700°C or 800°C; when the first temperature is lower than 500°C, the temperature is too low, the decomposition rate of carbonaceous gas is relatively slow, and the growth rate of carbon nanofibers also decreases; when the first temperature is higher than 800°C, the temperature is too high, which will cause the diameter of the carbon nanofibers to be larger, and in severe cases, it will block the pore structure of the porous carbon, which is not conducive to the deposition of nano-silicon.

[0089] In a preferred embodiment, the first duration is 20 minutes and the second duration is 1 hour.

[0090] The reaction conditions of this embodiment are conducive to ensuring reliable growth of carbon nanofibers, and are conducive to reducing production costs and ensuring safe operation.

[0091] In some embodiments, the flow rate of the reducing gas is 0.5 L / min-2 L / min, and the flow rate of the carbonaceous gas is 0.5 L / min-2 L / min.

[0092] Specifically, the flow rate of the carbonaceous gas can be but is not limited to 0.5L / min, 1L / min, 1.5L / min or 2L / min; when the flow rate of the carbonaceous gas is lower than 0.5L / min, the concentration of the carbonaceous gas in the reactor will be lower, and the number of carbon nanofibers generated will be smaller and unevenly distributed; when the flow rate of the carbonaceous gas is higher than 2L / min, this will promote the excessive conversion of the carbonaceous gas into carbon nanofibers, blocking the pore structure of the porous carbon.

[0093] The reducing gas flow rate and the carbonaceous gas flow rate of this embodiment are conducive to the reliable reduction growth of the carbonaceous gas to obtain carbon nanofibers.

[0094] In a preferred embodiment, the flow ratio of the inert gas to the carbonaceous gas is (0.1:9.9)-(9.9:0.1).

[0095] Specifically, the flow ratio of the inert gas to the carbonaceous gas can be but is not limited to 0.1:9.9, 0.2:9.8, 1:9, 2:8, 3.5:6.5, 1:1, 7:3, 8:2, 8.5:1.5, 9:1, 9.2:0.8 or 9.9:0.1, etc.; the ratio of the inert gas to the carbonaceous gas in this embodiment is appropriate, which is beneficial to control the concentration of the carbonaceous gas in the reactor body so that the generated carbon nanofibers have a uniform morphology.

[0096] In a preferred embodiment, the carbonaceous gas includes methane and / or acetylene.

[0097] In this embodiment, the carbonaceous gas has a simple molecular structure and is easy to decompose, so it is easier to grow carbon nanofibers at high temperatures.

[0098] In some embodiments, the catalyst includes at least one of a metal iron salt, a metal cobalt salt, a metal nickel salt, and a metal copper salt; In a preferred embodiment, the catalyst includes at least one of ferric chloride, cobalt chloride, cupric chloride, cobalt nitrate, nickel nitrate, nickel acetate, and copper sulfate.

[0099] The catalyst in this embodiment has readily available raw materials and low cost.

[0100] In some embodiments, based on the mass of the carbon matrix, the mass percentage of the catalyst is 0.1%-5%.

[0101] Specifically, the mass percentage of the catalyst can be but is not limited to 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4% or 5%. When the mass percentage of the catalyst is lower than 0.1%, the catalyst content is too low to be evenly dispersed on the carbon matrix, which may result in the inability to reliably grow carbon nanofibers inside the pores of the carbon matrix; when the mass percentage of the catalyst is higher than 5%, the catalyst content is too high, the catalyst is stacked on the carbon matrix, thereby affecting the catalytic active sites, and carbon nanofibers cannot be grown in the ideal position.

[0102] As an achievable manner, S20, before introducing a gaseous silicon source into the first product for heat treatment to obtain a second product, the method further comprises: The first product is sequentially acid-washed, water-washed, and dried.

[0103] Wherein, the acid includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

[0104] In this embodiment, acid washing is beneficial to remove the catalyst and other impurities remaining in the first product.

[0105] In some embodiments, S20, introducing a gaseous silicon source into the first product and heat treating the first product to obtain a second product comprises: The first product is heated to a second temperature at a second heating rate and maintained under the protection of an inert gas, and then a gaseous silicon source is introduced to carry out a constant temperature reaction for a third time period.

[0106] This embodiment is conducive to removing oxygen from the system, ensuring that silicon-based materials can be reliably deposited after the gaseous silicon source is introduced, and preventing the gaseous silicon source from undergoing other reactions at high temperatures to produce impurities.

[0107] As an optional solution, the second heating rate is 0.2°C / min-10°C / min, the second temperature is 500°C-800°C, and the third time is 0.1h-10h.

[0108] Specifically, the second heating rate may be, but is not limited to, 0.2°C / min, 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min; The second temperature may be, but is not limited to, 500°C, 600°C, 700°C or 800°C, etc. When the second temperature is lower than 500°C, the temperature is too low to achieve deposition of silicon-based materials; when the second temperature is higher than 800°C, the temperature is too high, which may cause larger silicon-based material particles.

[0109] The third time length can be but is not limited to 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h; when the first time length is lower than 0.1h, the reaction time is too short, resulting in the inability to deposit silicon-based materials from the gaseous silicon source; when the first time length is higher than 10h, the reaction time is too long, resulting in larger silicon-based material particles and increased costs.

[0110] In a preferred embodiment, the third duration is 1 hour to 4 hours.

[0111] The third duration of this embodiment is conducive to depositing silicon-based materials and is short in time, which is conducive to reducing costs.

[0112] As an achievable manner, the flow rate of the gaseous silicon source is 1 L / min-5 L / min.

[0113] Specifically, the flow rate of the gaseous silicon source can be but is not limited to 1L / min, 1.5L / min, 2L / min, 2.5L / min, 3L / min, 3.5L / min, 4L / min, 4.5L / min or 5L / min; when the flow rate of the gaseous silicon source is less than 1L / min, the flow rate of the gaseous silicon source is small, resulting in a lower content of silicon-based materials; when the flow rate of the gaseous silicon source is greater than 5L / min, the flow rate of the gaseous silicon source is large, which easily leads to larger silicon-based material particles.

[0114] In this embodiment, the flow rate of the gaseous silicon source is conducive to the reliable deposition of silicon-based materials, and the particle size of the deposited silicon-based materials will not be too large. The porous structure of the carbon matrix can provide a buffer space for the volume expansion of the silicon-based material during the charge and discharge process, which is conducive to improving the capacity performance and cycle stability of the negative electrode material.

[0115] In some embodiments, the gaseous silicon source includes at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.

[0116] The gaseous silicon source raw material of this embodiment is easily available and can reliably react to generate nano silicon particles at high temperature.

[0117] In some embodiments, S30, carbon-coating the second product to obtain a negative electrode material comprises: The second product and the carbon precursor are mixed and calcined to obtain the negative electrode material; wherein the mass ratio of the carbon precursor to the second product is 1:(0.5-3).

[0118] The calcination temperature is 800°C-900°C, and the calcination time is 2h-5h.

[0119] This embodiment is conducive to carbon coating the second product, further protecting the silicon-based material and improving the conductivity of the negative electrode material.

[0120] In summary, the method for preparing the negative electrode material of the embodiment of the present application is simple to operate, and can reliably grow carbon nanofibers in situ inside the pores of the carbon matrix, which is beneficial for the adhesion of silicon-based materials to the carbon nanofibers. In addition, through the reaction conditions and the amount of carbonaceous gas used, the carbon nanofibers form a cross-linked network structure, thereby forming a large number of conductive paths inside the pores of the carbon matrix, thereby improving the electrical conductivity of the negative electrode material.

[0121] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and the negative electrode material of the first aspect. Thus, the negative electrode has all the characteristics and advantages of the negative electrode material described above, which will not be repeated here. In general, the negative electrode sheet has good capacity performance and cycle stability.

[0122] In a fourth aspect, the present invention provides a battery comprising the negative electrode plate of the third aspect.

[0123] Therefore, the battery has all the characteristics and advantages of the negative electrode sheet mentioned above, which will not be repeated here. In general, the battery has good capacity performance and stability.

[0124] It is understandable that the battery may be a lithium-ion battery, a solid oxide battery, etc., and the embodiments of the present application do not specifically limit this.

[0125] In a fifth aspect, the present invention provides an electrical device, comprising the battery of the fourth aspect, wherein the battery supplies power to the electrical device.

[0126] Therefore, the electrical equipment has all the characteristics and advantages of the battery mentioned above, which will not be repeated here.

[0127] Specifically, the electrical device may be an electric vehicle, a hybrid vehicle, or an intelligent terminal device (such as but not limited to a mobile phone), etc.

[0128] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0129] Example 1 Preparation of negative electrode materials: Step 1, 10 g of phenolic resin-based porous carbon with a particle size of 8 μm and a pore size of 200 nm is selected, and the phenolic resin-based porous carbon is placed in 100 mL of ethanol. After magnetic stirring for 30 minutes, ferric chloride accounting for 1% of the mass of the phenolic resin-based porous carbon is added thereto, and after continuing to stir for 2 hours, suction filtration and vacuum drying are performed to obtain a pretreated product; Step 2, transferring the pretreated product to a chemical vapor deposition furnace, introducing argon gas to exclude air until the oxygen content is less than 100 ppm, heating to 600°C at a heating rate of 2°C / min and maintaining, first introducing hydrogen for 20 minutes, and then introducing acetylene for chemical vapor deposition, stopping the introduction of acetylene and hydrogen and stopping heating after 1 hour, and after cooling to room temperature, transferring the obtained product to a 0.1M HCL solution, acid washing, filtering, and drying to obtain a first product; wherein the flow rates of nitrogen, hydrogen, and acetylene are 2L / min, 1L / min, and 0.5L / min, respectively; Step 3, the first product is transferred to the vapor deposition furnace again, argon is introduced to remove oxygen in the furnace, the temperature is increased to 600°C at a heating rate of 2°C / min and maintained, SiH4 is introduced at a flow rate of 1.5L / min, and after reacting for 3h, the heating is stopped, argon is kept introduced and the mixture is naturally cooled to room temperature to obtain the second product; Step 4, the second product and coal tar pitch are put into a VC mixer at a mass ratio of 8:2, mixed for 40 minutes, and then transferred to a tubular furnace, heated to 900°C at a heating rate of 5°C / min under an argon atmosphere, and kept warm for 2 hours. After cooling to room temperature, the material is crushed and sieved to obtain a negative electrode material; Among them, the thickness of the carbon coating layer in the negative electrode material is ~12nm, and the specific surface area of ​​the material is 3.9m 2 / g, D50=8.3μm; the length of carbon nanofibers is ~130nm, and the diameter is ~30nm; the mass proportion of silicon in the negative electrode material is 46%, and the particle size of amorphous silicon is ~4.7nm.

[0130] Example 2 Different from Example 1, in step 1 of this embodiment, the catalyst ferric chloride accounts for 0.5% of the mass of the phenolic resin-based porous carbon; Example 3 Different from Example 1, in step 1 of this embodiment, the catalyst ferric chloride accounts for 2% of the mass of the phenolic resin-based porous carbon; Example 4 Different from Example 1, in step 1 of this embodiment, the catalyst ferric chloride accounts for 4% of the mass of the phenolic resin-based porous carbon; Example 5 Different from Example 1, in step 1 of this embodiment, the catalyst ferric chloride accounts for 5% of the mass of the phenolic resin-based porous carbon; Example 6 Different from Example 1, in step 1 of this embodiment, the catalyst ferric chloride accounts for 8% of the mass of the phenolic resin-based porous carbon; Example 7 Different from Example 1, the flow rate of acetylene in step 2 in this embodiment is 0.2 L / min; Example 8 Different from Example 1, the flow rate of acetylene in step 2 of this embodiment is 1L / min Example 9 Different from Example 1, the flow rate of acetylene in step 2 of this embodiment is 2L / min Example 10 Different from Example 1, the temperature in step 2 of this embodiment is 400°C; Embodiment 11 Different from Example 1, the temperature in step 2 of this embodiment is 500°C; Example 12 Different from Example 1, the temperature in step 2 of this embodiment is 800°C; Embodiment 13 Different from Example 1, the temperature in step 2 of this embodiment is 1000°C; Embodiment 14 Different from Example 1, the flow rate of SiH4 in step 3 in this embodiment is 1 L / min; Embodiment 15 Different from Example 1, the flow rate of SiH4 in step 3 in this embodiment is 5 L / min; Example 16 Different from Example 1, the flow rate of SiH4 in step 3 in this embodiment is 8 L / min; Embodiment 17 Different from Example 1, the flow rate of SiH4 in step 3 in this embodiment is 0.5 L / min; Comparative Example 1 Different from Example 1, this comparative example does not include step 2; Comparative Example 2 Different from Example 1, porous carbon is not used in this comparative example; Comparative Example 3 Different from Example 1, this comparative example does not include step 3; Comparative Example 4 Different from Example 1, this comparative example does not include step 4.

[0131] The following describes the battery performance test process and test results: The negative electrode material prepared in the embodiment and the comparative example was mixed with carbon black (SP), sodium carboxymethyl cellulose (CMC), carbon nanotubes (CNT), and a binder (SBR) in a mass ratio of 95%:2%:0.5%:0.5%:2% to prepare a negative electrode slurry. The mixed slurry was coated on a copper foil, dried in a forced air drying oven, cut into circular electrode sheets with a diameter of 12 mm, rolled to a certain thickness, and then transferred to a glove box for use in assembling batteries.

[0132] The assembly of the button battery was carried out in a glove box containing argon gas, with lithium sheets as counter electrodes, the electrolyte being 1 mol / L lithium hexafluorophosphate / ethylene carbonate + dimethyl carbonate + diethyl carbonate (v / v=1:1:1), and the separator being Celgard2400, assembled into a button battery. The charge and discharge of the lithium-ion battery was carried out on a LAND battery test device, with a discharge cut-off voltage of 0.005 V and a charge cut-off voltage of 1.5 V. The charge and discharge test was carried out at a current density of C / 10, and the test results are recorded in Table 1. The first charge and discharge curve is shown in Table 1. Figure 3 shown.

[0133] from Figure 3 It can be seen that Example 1 has a higher discharge specific capacity of 1510 mAh / g.

[0134] The results of the batteries of Examples 1-17 and Comparative Examples 1-4 tested according to the above process and method are shown in Table 1: Table 1 Test results of Examples 1-17 and Comparative Examples 1-4

[0135] The scanning electron microscope photo of the negative electrode material prepared in Example 1 is as follows Figure 2 As shown, from Figure 2 It can be seen that the prepared silicon-carbon composite negative electrode material has a uniform morphology.

[0136] According to the results shown in Table 1: According to Examples 1-13, the mass percentage of the catalyst, the mass percentage of the carbonaceous gas, and the reaction temperature disclosed in the examples of the present application are conducive to the negative electrode material having a higher capacity and good cycle performance. When there is too much catalyst, the reaction temperature is too high, or the flow rate of the carbonaceous gas is too low, the capacity performance of the negative electrode material is uniformly reduced; and as the mass percentage of the catalyst, the acetylene flow rate, and the reaction temperature increase, the silicon content of the negative electrode material decreases; According to Examples 14-17, it can be seen that the flow rate of silane gas in the embodiments of the present application is conducive to the negative electrode material having higher capacity performance and good cycle stability; and when the flow rate of silane gas is large, the amount of nano-silicon in the negative electrode material also increases, which is conducive to increasing the gram capacity of the negative electrode material, but the cycle performance of the negative electrode material is slightly reduced. This may be because the excessively generated nano-silicon will continue to deposit on the surface of the porous carbon, weakening the cycle performance of the material.

[0137] According to the test results of Examples 1-17 and Comparative Examples 1-4, the negative electrode materials of the embodiments of the present application have both good capacity performance and cycle performance.

[0138] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A negative electrode material, characterized in that: It comprises a core and a carbon coating layer coated outside the core; wherein the core comprises: A carbon matrix having a porous structure; Carbon nanofibers are located inside the pores of the carbon matrix, and the carbon nanofibers are cross-linked to form a network structure inside the pores of the carbon matrix; The silicon-based material is distributed inside the pores of the carbon matrix and on the carbon nanofibers.

2. The negative electrode material according to claim 1, characterized in that The pores of the carbon matrix have a pore diameter of 30nm-500nm; Optionally, the average particle size of the carbon matrix is ​​2 μm-30 μm.

3. The negative electrode material according to claim 1, characterized in that The length of the carbon nanofiber is 20nm-1000nm, and the diameter of the carbon nanofiber is 10nm-100nm.

4. The negative electrode material according to claim 1, characterized in that Based on the mass of the negative electrode material, the mass percentage of the silicon-based material is 30%-95%; Optionally, the average particle size of the silicon-based material is 2 nm-10 nm.

5. The negative electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area of ​​the negative electrode material is 2m 2 / g-5m 2 / g; Optionally, the median particle size of the negative electrode material is 5 μm-40 μm.

6. The negative electrode material according to any one of claims 1 to 4, characterized in that: The carbon nanofibers are also distributed on the surface of the carbon matrix, and two ends of the carbon nanofibers located on the surface of the carbon matrix are in contact with the carbon matrix and the carbon coating layer, respectively.

7. The negative electrode material according to any one of claims 1 to 4, characterized in that: The thickness of the carbon coating layer is 10nm-2000nm.

8. A method for preparing the negative electrode material according to any one of claims 1 to 7, characterized in that: include: The carbon matrix and the catalyst are introduced into a reducing gas and a carbonaceous gas under the protection of an inert gas, and subjected to a heat treatment to obtain a first product; wherein the carbonaceous gas includes a gas that can be cracked to obtain carbon after the heat treatment; The first product is introduced into a gaseous silicon source and subjected to heat treatment to obtain a second product; The second product is carbon-coated to obtain the negative electrode material.

9. The method according to claim 8, characterized in that The carbon matrix and the catalyst are introduced into a reducing gas and a carbonaceous gas under the protection of an inert gas, and heat-treated to obtain a first product, comprising: The carbon matrix and the catalyst are heated to a first temperature at a first heating rate and maintained under the protection of an inert gas. After the reducing gas is introduced for a first period of time, the carbonaceous gas is introduced while the reducing gas is continued to be introduced, and the first product is obtained by heat treatment for a second period of time.

10. The method according to claim 9, characterized in that The first heating rate is 2°C / min-10°C / min, the first temperature is 500°C-800°C, the first time length is 10min-20min, and the second time length is 0.5h-1.5h.

11. The method according to claim 8, characterized in that The flow rate of the reducing gas is 0.5L / min-2L / min, and the flow rate of the carbonaceous gas is 0.5L / min-2L / min.

12. The method according to claim 8, characterized in that The flow ratio of the inert gas to the carbonaceous gas is (0.1:9.9)-(9.9:0.1).

13. The method according to claim 8, characterized in that The carbonaceous gas includes methane and / or acetylene.

14. The method according to claim 8, characterized in that The catalyst comprises at least one of a metal iron salt, a metal cobalt salt, a metal nickel salt and a metal copper salt; Preferably, the catalyst includes at least one of ferric chloride, cobalt chloride, cupric chloride, cobalt nitrate, nickel nitrate, nickel acetate, and copper sulfate.

15. The method according to claim 8, characterized in that Based on the mass of the carbon matrix, the mass percentage of the catalyst is 0.1%-5%.

16. The method according to claim 8, characterized in that Before introducing a gaseous silicon source into the first product and subjecting it to a heat treatment to obtain a second product, the method further comprises: The first product is sequentially acid-washed, water-washed, and dried.

17. The method according to claim 8, characterized in that The first product is introduced into a gaseous silicon source and heat-treated to obtain a second product, comprising: The first product is heated to a second temperature at a second heating rate and maintained under the protection of an inert gas, and then the gaseous silicon source is introduced to carry out a constant temperature reaction for a third time period.

18. The method according to claim 17, characterized in that The second heating rate is 0.2°C / min-10°C / min, the second temperature is 500°C-800°C, and the third time is 0.1h-10h; Preferably, the third duration is 1h-4h.

19. The method according to claim 8, characterized in that The flow rate of the gaseous silicon source is 1L / min-5L / min; Optionally, the gaseous silicon source includes at least one of monosilane, disilane, monochlorosilane and dichlorosilane.

20. The method according to claim 8, characterized in that The step of carbon-coating the second product to obtain the negative electrode material comprises: The second product and the carbon precursor are mixed and calcined to obtain the negative electrode material; wherein the mass ratio of the carbon precursor to the second product is 1:(0.5-3).

21. A negative electrode sheet comprising a current collector and the negative electrode material according to any one of claims 1 to 7.

22. A battery, characterized in that: Includes the negative electrode sheet as described in claim 21.

23. An electrical equipment, characterized in that: The battery according to claim 22 is used to supply power to the electrical device.